Morphological and Chemical Characterization of Aconitum heterophyllum, a Critically Endangered Himalayan Medicinal Plant (Advances in Applied Biological Research, 2026)
Aconitum heterophyllum Wall. ex Royle is a critically endangered Himalayan  medicinal herb extensively used in traditional medicine for its analgesic, antipyretic,  and anti-inflammatory properties. The present study evaluated the species through  morphological characterization, qualitative phytochemical screening, and GC– MS profiling of methanolic root extracts. Morphological observations confirmed  diagnostic features such as paired tuberous roots, palmately lobed leaves,  and racemose inflorescences, supporting species authentication. Preliminary  phytochemical analysis revealed the presence of alkaloids, carbohydrates, lipids/ fatty acids, and phenolic compounds, whereas flavonoids and saponins were absent.  GC–MS analysis identified ten major compounds, predominantly α-linolenic acid,  palmitic acid, fatty acid esters, carbohydrate derivatives, and nitrogen-containing  metabolites. The findings indicate a chemically diverse metabolite profile with  potential antioxidant and anti-inflammatory significance. However, the study  also recognizes the limitations of GC–MS in detecting thermolabile diterpenoid  alkaloids characteristic of Aconitum species. Overall, the study establishes baseline  pharmacognostic and chemical markers useful for authentication, quality  evaluation, conservation planning, and future LC–MS/MS- based metabolomic  investigations of this threatened Himalayan medicinal plant.
Keywords: Aconitum heterophyllum; pharmacognosy; phytochemical screening; GC–MS; alkaloids; fatty acids.